2018
DOI: 10.1109/tit.2017.2679053
|View full text |Cite
|
Sign up to set email alerts
|

R-FFAST: A Robust Sub-Linear Time Algorithm for Computing a Sparse DFT

Abstract: The Fast Fourier Transform (FFT) is the most efficiently known way to compute the Discrete Fourier Transform (DFT) of an arbitrary n-length signal, and has a computational complexity of O(n log n). If the DFT X of the signal x has only k non-zero coefficients (where k < n), can we do better? In [1], we addressed this question and presented a novel FFAST (Fast Fourier Aliasing-based Sparse Transform) algorithm that cleverly induces sparse graph alias codes in the DFT domain, via a Chinese-Remainder-Theorem (CRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The researcher adopted the FFAST framework to the case that is corrupted by white Gaussian noise. The author showed that the extended noise-robust algorithm R-FFAST [6], [7] computes the DFT using O(K logK ) samples in O(K log 4 N ) runtime. These two algorithms perform well when N is a product of some smaller prime numbers.…”
Section: Introductionmentioning
confidence: 99%
“…The researcher adopted the FFAST framework to the case that is corrupted by white Gaussian noise. The author showed that the extended noise-robust algorithm R-FFAST [6], [7] computes the DFT using O(K logK ) samples in O(K log 4 N ) runtime. These two algorithms perform well when N is a product of some smaller prime numbers.…”
Section: Introductionmentioning
confidence: 99%
“…For the complexity of recovery algorithm, the ℓ 1 norm minimization has a computation complexity of O( 3 ). To reduce this complexity, with the sparse measurement matrices, various low computational complexity message-passing algorithms have been introduced for reconstruction of sparse signals in CS [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In [9], the authors used the random sparse matrix as a new sparse measurement matrix and proposed an iterative algorithm of complexity of O( log( ) log( )), while it only required = O( log( )) measurements.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the restriction of the decoding algorithms discussed above, Pawar et al in [19][20][21][22] designed a hybrid mix of the LDPC codes and Discrete Fourier Transform (DFT) framework (LDPC-DFT) and proposed a fast Short-and-Wide Iterative Fast Transform (SWIFT) peeling decoding recovery algorithm. It only needs O( ) measurements and O( ) iterative step to achieve the exact signal recovery in the noiseless case.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations